Non-genomic mechanisms of progesterone action in the brain - Singh, Meharvan; Su, Chang; Ng, Selena (Frontiers in Neuroscience, 2013)
Progesterone is a gonadal steroid hormone whose physiological effects extend well beyond the strict confines of reproductive function. In fact, progesterone can have important effects on a variety of tissues, including the bone, the heart and the brain. Mechanistically, progesterone has been thought to exert its effects through the progesterone receptor (PR), a member of the nuclear steroid hormone superfamily, and as such, acts through specific progesterone response elements (PRE) within the promoter region of target genes to regulate transcription of such genes. This has been often described as the “genomic” mechanism of progesterone action. However, just as progesterone has a diverse range of tissue targets, the mechanisms through which progesterone elicits its effects are equally diverse. For example, progesterone can activate alternative receptors, such as membrane-associated progesterone receptors (distinct from the classical PR), to elicit the activation of several signaling pathways that in turn, can influence cell function. Here, we review various non-nuclear (i.e., non-genomic) signaling mechanisms that progesterone can recruit to elicit its effects, focusing our discussion primarily on those signaling mechanisms by which progesterone influences cell viability in the brain.